Comparison of Whistle-blower Protection Mechanism of Select Countries. Issue 1 (June 2018) - Sharma, J. P.; Kanojia, Sunaina; Sachdeva, Shikha
Abstract: Whistle-blower protection mechanisms (WPMs) play a critically significant role in combating corruption through ethics, corporate governance and statutes. This article examines the essence of whistle-blower mechanism existing in the developed and developing countries in order to unearth the legislative structure of countries supporting the whistle blower mechanism and pursuit of ethical conduct for sound corporate governance. The article attempts to identify, evaluate and analyse the attributes of whistle-blower mechanism across nations and finds that despite off-symmetric attributes, the mechanisms are asymmetric specific to the countries' corporate culture. It has also been found that most significant attribute of a sound whistle-blower mechanism is the level of protection provided to the whistle-blowers followed by coverage of sectors, anonymity and the regulator of whistle-blowing complaints in the country. The attributes vary widely across nations on the basis of coverage of sectors, anonymity withheld and the level of protection, with United States of America delivering the best protection to whistle-blowers trailed by Australian whistle-blower protection laws and then South Africa; India, China and Indonesia lag considerably behind in having a sound whistle-blower mechanism.